Angiographic CT: in vitro comparison of different carotid artery stents : does stent orientation matter? - Lettau, Michael; Bendszus, Martin; Hähnel, Stefan (Neuroradiology, 2013)
Introduction Our aim was to evaluate the in vitro visualization of different carotid artery stents on angiographic CT (ACT). Of particular interest was the influence of stent orientation to the angiography system by measurement of artificial lumen narrowing (ALN) caused by the stent material within the stented vessel segment to determine whether ACT can be used to detect restenosis within the stent. Methods ACT appearances of 17 carotid artery stents of different designs and sizes (4.0 to 11.0 mm) were investigated in vitro. Stents were placed in different orientations to the angiography system. Standard algorithm image reconstruction and stent-optimized algorithm image reconstruction was performed. For each stent, ALN was calculated. Results With standard algorithm image reconstruction, ALN ranged from 19.0 to 43.6 %. With stent-optimized algorithm image reconstruction, ALN was significantly lower and ranged from8.2 to 18.7 %. Stent struts could be visualized in all stents. Differences in ALN between the different stent orientations to the angiography system were not significant. Conclusion ACT evaluation of vessel patency after stent placement is possible but is impaired by ALN. Stent orientation of the stents to the angiography system did not significantly influence ALN. Stent-optimized algorithm image reconstruction decreases ALN but further research is required to define the visibility of in-stent stenosis depending on image reconstruction.